Negotiating a Career Path<subtitle>Women Artists in Norway after 1900</subtitle> - Signe Endresen (Kunst og Kultur)
Norwegian artists that began exhibiting their work around 1900–1910 had vastly different career trajectories depending on their gender. The article highlights the career trajectories of five women, all of whom were all students at Harriet Backer’s art school. The women received the same training as the men. A combination of factors (political, economic, social, critical reception, etc.) affected this generation of women artists particularly hard, while the men became central to the development of modern art in Norway.